Christianity and Local Wisdom: Contextualising Worship in Chinese Culture - Susanto Susanto; Tonny Andrian Stefanus; Maria Titik Windarti (International Perspectives in Christian Education and Philosophy, 2025)
This article explores the contextualisation of Christianity within Chinese culture by examining how Christian worship can embrace local wisdom and cultural values. Contextualisation plays a crucial role in ensuring that the expression of Christian faith remains both theologically sound and cul-turally resonant. In the Chinese context, where ancestral reverence, symbolic traditions, and fami-ly-centered values are deeply embedded, a sensitive and thoughtful approach is required. The study employs a qualitative method through a literature review of theological writings, historical records, and cultural analyses to investigate how Christian theology can engage meaningfully with Chinese traditions. The findings reveal that certain cultural elements—such as ancestor honour, which is central to filial piety; the colour red, symbolising prosperity and joy; and the collectivist view of family—can be reinterpreted within a Christian framework. Ancestor honour, for instance, can be seen not as idol worship but as a celebration of faith heritage and family lineage. The use of tradi-tional music, symbols, and festivals such as Chinese New Year in church services demonstrates that cultural integration is possible without compromising the gospel's core message.Moreover, the emphasis on harmony and extended family in Chinese society parallels the Christian concept of koinonia, or spiritual fellowship. By embracing these cultural values, churches in China can present the Christian faith in ways that are both biblically faithful and culturally meaningful. This research underscores the importance of contextual theology in nurturing indigenous expressions of Chris-tianity that honor both Christ and culture.